Green manuring: its effect on soil properties and crop growth under rice–wheat cropping system - Mandal, Uttam Kumar; Singh, Gurcharan; Victor, U.S; Sharma, K.L (European journal of agronomy, 2003)
A field experiment was conducted on rice ( Oryza sativa L.) and wheat ( Triticum aestivum L.) during rainy and winter seasons of 1994–95 in a clay loam soil (Typic Ustochrept) at the experimental farm of Indian Agricultural Research Institute, New Delhi, India. The objectives were to study the influence of different green manuring ( Sesbania rostrata, Sesbania aculeata, green gram ( Vigna radiata) residues) and in combination with different levels of nitrogen (0, 60, and 120 kg N ha −1) on physical properties, organic matter and total nitrogen contents of soil and on root growth and spectral response of rice and wheat crop. The organic matter and total soil nitrogen concentrations were found to be higher under green manuring treated plots than summer fallow. The magnitude of reduction in bulk density due to green manuring over fallow was 0.03–0.07 Mg m −3 in 0–15 cm soil layer and 0.05–0.09 Mg m −3 in 15–30 cm soil layer during the growth of rice and wheat. Green manuring improved the soil physical environments as was evident from higher values of mean weight diameter and saturated hydraulic conductivity than fallow. The better physical and chemical environment in Sesbania ( S) and green gram residue incorporated plots influenced higher Normalized Difference Vegetation Index (NDVI) than under fallow. The NDVI attained peak values at 62 days after transplanting of rice and 90 days after sowing of wheat. The root length density (RLD) and yields were higher in green manure plots than in fallow both in rice as well as in succeeding wheat crop. In all cases, in both rice and wheat the application of 120 kg N ha −1 treatment resulted in higher RLD than 60 kg N ha −1 and no nitrogen treatments. Poor soil conditions were mainly responsible for restricted root growth and its distribution in surface soil layer in summer fallow plots.